Human leukocyte antigen (HLA) class II association in chronic hepatitis B patients with hepatocellular carcinoma in a Malay population: a pilot study - Krishnan, Prasobhan Bala; Abdullah, Maha; Shuaibu, Hudu Abdullahi; Sekawi, Zamberi; Tan, Soek Siam; Amin Nordin, Syafinaz (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Asian countries account for almost three quarter of hepatocellular carcinoma (HCC) reported globally and chronic hepatitis B infection is one of the main contributors. Clinical observations show that Malay patients with chronic hepatitis B and HCC tend to have a worse outcome, when compared to other two major races in Malaysia. The objectives of this study was to determine the frequency of human leukocyte antigen (HLA) class II alleles in chronic hepatitis B patients with HCC among Malays compared to the general population to identify potential associations of HLA alleles with this disease. HLA class II typing was performed in chronic hepatitis B patients with hepatocellular carcinoma (n=12) by –polymerase chain reaction, sequence specific primer (PCR-SSP) method. There were higher allelic frequencies of certain HLA-DQB1 and HLA-DRB1 alleles; HLA-DQB1*03 (07) (41.7%), and HLA-DRB1*12 (41.7% vs 28.6%) and compared to controls (41.7% vs 29.7%). However, there was no significant statistical correlation found when compared with the normal healthy general population. This study provides an insight into the HLA Class II association with chronic hepatitis B and hepatocellular carcinoma in Malays. However, findings from this study should be validated with a larger number of samples using a high resolution HLA typing